2019
DOI: 10.1007/s11085-019-09946-6
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Element Effects in High-Temperature Alloys Disentangled

Abstract: Reactive elements-REs-are decisive for the longevity of high-temperature alloys. This work joins several previous efforts to disentangle various RE effects in order to explain apparently contradicting experimental observations in alumina forming alloys. At 800-1000 °C, "messy" aluminum oxy-hydroxy-hydride transients initially formed due to oxidation by H 2 O which in turn undergo secondary oxidation by O 2. The formation of the transient oxide becomes supported by dispersed RE oxide particles acting as water e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 45 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…A relatively large difference in thermal expansion between the oxide scale and substrate was the cause of scale spallation. The addition of small amounts of elements of Ce, Hf, Y, or Zr less than 1% is expected and can increase the spalling resistance of the oxide scales [59,60].…”
Section: Surface Oxides From Xrd Resultsmentioning
confidence: 99%
“…A relatively large difference in thermal expansion between the oxide scale and substrate was the cause of scale spallation. The addition of small amounts of elements of Ce, Hf, Y, or Zr less than 1% is expected and can increase the spalling resistance of the oxide scales [59,60].…”
Section: Surface Oxides From Xrd Resultsmentioning
confidence: 99%
“…Once a dense and continuous Al2O3 layer formed in the corrosion product scale, the inward diffusion of corrosive media such as O, S, Cl, etc., will be effectively inhibited. Studies have shown that both Co and Y can promote the selective oxidation of Al to form a continuous Al2O3 protective layer [15,31,32].…”
Section: Morphology Of Hot Corrosion Productsmentioning
confidence: 99%
“…Small additions of so-called reactive elements (RE), e.g., Y, Zr, Hf, and Ce, either in elemental form or dispersed RE oxide particles, to enhance the oxidation performance and lifespan of alumina-forming high-temperature alloys have been widely documented and studied [33,41,54,55]. The beneficial effects for RE addition include remarkably improved scale adherence, suppression of convoluted oxide scale morphology and void formation, enhanced selective Al oxidation and altering scale growth mechanism from both anion and cation to predominant anion diffusion.…”
Section: Effect Of Reactive Elementsmentioning
confidence: 99%